Direct optical observation of solid electrolyte interphase formation dynamics in lithium-ion batteries - Wenlong Li; Tianxiao Sun; Sameep Rajubhai Shah; Zhengyu Ju; Jigang Zhou; Kejie Zhao; Guihua Yu; Yijin Liu (Proceedings of the National Academy of Sciences, 2026)
Lithium-ion battery formation is a pivotal step that dictates performance, longevity, and manufacturing safety. At the core of this process is the formation and evolution of the solid electrolyte interphase (SEI), whose nanoscale thickness, high environmental sensitivity, and dynamic behavior have long hindered direct characterization. Here, we exploit the SEI-induced refractive index matching effect and utilize operando optical microscopy to directly visualize SEI growth in real time. Our observations reveal pronounced lateral heterogeneity and asynchronicity during the first lithiation of graphite anodes. Surprisingly, high formation current promotes synchronized SEI growth, leading to a more uniform SEI coverage. Building on this mechanistic insight, we designed a pulsed high-current formation protocol for 2 Ah LiFePO 4 (LFP)/graphite pouch cells, achieving nearly an order-of-magnitude reduction in formation time while simultaneously enhancing the cycling performance. These findings challenge the prevailing belief that low currents are essential for developing a uniform SEI and pave a path toward safer and more efficient large-scale battery production.